Comparative evaluation and comparability of satellite and airborne data on the ice content of the Sea of Okhotsk - V. A. Romanyuk; G. G. Zhuravlev (Лëд и снег, 2015)
Information on the sea ice coverage is one of the most important for the development of the Sakhalin shelf. The paper deals with the evaluation of ice extent estimations in the Sea of Okhotsk based on data of the remote sensing and aerial observations in winter seasons 1970–1991. The analysis has revealed the average seasonal difference in satellite and aerial ice series is 120.2 thousand km² (7.5% of the sea area). Ranges of changes of average values of a difference for a season has made from 18.5 to 265.6 square kilometers. The satellite and aerial sea ice extent data are strongly correlated (R = 0.96) with high significance for all period considered. The results obtained suggest that the series of observations of ice cover of the Sea of Okhotsk, made by different methods, have good comparability and can be used together to complement each other and produce an integrated and refined sea ice maps.